Marketing Capability in Production Facility Procurement Projects: A Value Creation Perspective in the Manufacturing Industry - Sukardi Sukardi; Ith Vuthy (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
This study aims to analyze marketer capabilities in production facility procurement projects within the manufacturing industry from a value creation perspective. In increasingly complex industrial project environments, the role of marketers extends beyond traditional selling activities to encompass the ability to integrate technical, relational, and business dimensions in addressing customer needs. This research adopts a qualitative conceptual approach using a literature review method, examining relevant theories on marketing capabilities, value creation, and business-to-business (B2B) project marketing. The study was conducted systematically over a six-month period, from September to November 2025, covering stages of literature identification, selection, analysis, and conceptual synthesis. The study integrates the perspectives of Service-Dominant Logic (SDL) and Goods-Dominant Logic (GDL) to explain that value creation in production facility procurement projects is derived not only from the product as a tangible output but also from the services and interactions that accompany it. The findings indicate that marketer capabilities include technical understanding, relational competence, value communication, and project risk management, as well as the ability to integrate product-based and service-based value into comprehensive solutions. These capabilities play a critical role in shaping customer-perceived value, which ultimately influences purchasing decisions and overall project success. The study highlights that value integration capability serves as a key differentiator in project marketing performance. From a managerial perspective, firms are encouraged to develop integrated marketer capabilities as part of a value-driven business strategy to enhance competitiveness in the manufacturing sector.